An Analysis on Various Effective Techniques For Developing Entrepreneurial Life Skills In Schools: Exploring the Impact of School-Industry Link on Entrepreneurial and Life Skills Education (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The need to developentrepreneurial skills among students in the classroom has taken a globaldimension due to growing graduate unemployment and economic recession.School-industry link is one of the pedagogy practices to enhance studentslearning of entre page | entrepreneurial skills in the classroom. Linkagesbetween educational institutions and industries allow students to explore theopportunities of self-employment through the practical and direct involvementof local businesses. This paper looked at the concept of entrepreneurship andentrepreneurship education as well as the objectives and importance ofentrepreneurship education. It established the importance of school-industrylinks in imparting entrepreneurial skills to students in the classroom, andexamined different strategies for inculcating entrepreneurship skills. It alsoidentified some problems and prospects in adopting different strategies inimparting entrepreneurial skills in classroom. School is the platform for learning for the student. Themain objectives of school are to build a productive generation in the future.The teacher focuses on the overall development of the students. Teacher buildsreading writing and arithmetic skills among students. Apart from these skillsit is the duty of the teacher as well as school setting to enable the studentsto face challenges in life. It is the generic life skills like self-awareness,empathy, effective communication, inter personal relationship, problem solving,decision making, creative and critical thinking, coping with stress andemotions that help the students to overcome challenges in real life. In thisstudy the researchers aims to identify the importance of life skills educationin school setting and identifying the gap in providing this life skills inschool setting.